The Oxford handbook of Isaiah - Tiemeyer, Lena-Sofia (Oxford handbooks online Religion, 2020)
The book of Isaiah is without doubt one of the most important books in the Hebrew Bible/Old Testament, as evidenced by its pride of place in both Jewish and Christian traditions as well as in art and music. Most people, scholars and laity alike, are familiar with the words of Isaiah accompanied by the magnificent tones of Handel's 'Messiah'. Isaiah is also one of the most complex books due to its variety and plurality, and it has accordingly been the focus of scholarly debate for the last 2000 years.